2017
DOI: 10.1038/cddiscovery.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Protection of the biconcave profile of human erythrocytes against osmotic damage by ultraviolet-A irradiation through membrane-cytoskeleton enhancement

Abstract: To perform various physiological functions, erythrocytes possess a unique biconcave shape provided by a special architecture of the membrane-skeleton system. In the present work, we use a simple irradiation method to treat human erythrocytes with 365 nm ultraviolet-A (UVA) light at the single-cell level in vitro. Depending on the irradiation dose, UVA show protection of the biconcave profile against the detrimental action of distilled water. This protective effect can also be confirmed for saponin that damages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…32 Because trypan blue can only stain dead cells with damaged membranes, it cannot stain live cells with impermeable membranes. 33 Cell viability is generally defined as a percentage of living cells in a whole population. 34 However, some cells that have lost their metabolic capacity but have not died are identified as living cells, resulting in inaccurate cell viability assessments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Because trypan blue can only stain dead cells with damaged membranes, it cannot stain live cells with impermeable membranes. 33 Cell viability is generally defined as a percentage of living cells in a whole population. 34 However, some cells that have lost their metabolic capacity but have not died are identified as living cells, resulting in inaccurate cell viability assessments.…”
Section: Resultsmentioning
confidence: 99%
“…The trypan blue method is the gold standard for calculating cell viability but is inaccurate for assessing cell viability below 80% . Because trypan blue can only stain dead cells with damaged membranes, it cannot stain live cells with impermeable membranes . Cell viability is generally defined as a percentage of living cells in a whole population .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that ROS can impact the polarization and activation of M1-like macrophages by regulating the signal transduction pathways of mitogen-activated protein kinase (MAPK) and NF- κ B, which are linked to pro-inflammatory gene expression [ [15] , [16] , [17] ]. Furthermore, ROS generation can be stimulated through light irradiation, resulting in a targeted and localized effect with minimal adverse effects [ 18 , 19 ]. In immunotherapy, small molecule drugs, particularly ROS photosensitizers, have gained prominence [ 20 ].…”
Section: Introductionmentioning
confidence: 99%